Are consumers attentive to local energy costs? Evidence from the appliance market - Sébastien Houde; Erica Myers (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
We estimate whether consumers respond to local energy costs when purchasing appliances. Using a dataset from an appliance retailer, we compare demand responsiveness to a measure of energy costs that varies with local energy prices versus purchase prices. We strongly reject that consumers are unresponsive to local energy costs under a wide range of assumptions. These findings run counter to the popular wisdom, which motivates energy standards, that energy costs are a shrouded attribute. Capital investments are an important channel for electricity demand response and may explain some of the large differences between short and long run electricity price elasticities
Keywords: Q41; Q50; L15; D12; D83; 330; inattention; shrouded attributes; energy efficiency gap; misperceptions; appliance efficiency standards